إفشاء الموظف العمومي للسر المهني في التشريع الجزائري - • لعلي توفيق • طوينة عادل (جامعة المسيلة, 2021)
مع تطور المجتمعات والدول بدا الاهتمام بسر المهنة ،واعتبرتها التشريعات من الواجبات أو الالتزامات التي تقع على عاتق أصحاب المهن والوظائف المختلفة ، ونجد بان هؤلاء ملزمون بالحفاظ عل السر المهني وعدم إفشائه للغير ، وقد تضمنت كافة القوانين والتشريعات واجب الحفاظ على الأسرار وتجريم إفشائها ، نظرا لخطورتها أوالأضرار التي تسببها للأفرادأو الدول جزاء هذا الإفشاء ، ولقد أحاطت التشريعات الإسلامية وكذا القانون الجزائري سر المهنة بحماية جزائية خاصة ، وذلك من اجل حماية الأفراد وحماية المصلحة العامة ، لكن في بعض الحالات يكون المؤتمن على السر مضطرا لإفشاء السر وذلك حماية للمصلحة العامة ، حيث أجاز له القانون ذلك ورخص له القضاء الخروج عن السر المهني إذ كان يقصد من ذلك حماية الصالح العام ، حيث يتعين على المهني إفشاء السر كلما دعت الحاجة إلى ذلك ، ومثال على ذلك انتشار الأمراض المعدية( كفيروس كورونا ) أو الجرائم ، والعمل على كتمانها يؤدي إلى تفشيها وإلحاق الضرر بالمصلحة العامة ، لكن هذا لا يعنيالإفشاء المطلق للسر ، ومن خلال هذا يمكن القول بان السر المهني لم يعد عقبة أمام حماية المصلحة العامة ، فالمؤتمن على السر المهني يمكن له إفشاء السر كلما اقتضت الحاجة لذلك مع واجب احترام القيود التي نص عليها القانون ، فإذا خافها المهني أو تجاوزها يعد مفشيا للسر ويعاقب وفقا للنصوص القانونية . Summary: With the development of societies and countries, interest in the secret of the profession began, and legislation considered it one of the duties or obligations of the owners of various professions and jobs, and we find that these are obligated to maintain professional secrets and not disclose it to others, and all laws and legislation included the duty to preserve secrets and criminalize their disclosure, due to its seriousness and the dangers it causes to individuals or countries as a penalty for this disclosure . Islamic legislation as well as Algerian law has surrounded the profession’s secret with special penal protection, in order to protect individuals and protect the public interest, but in some cases the person entrusted with the secret is obliged to disclose the secret in order to protect the public interest, as The law allowed him to do so and the judiciary authorized him to deviate from the professional secret if it was intended to protect the public interests, as the professional must disclose the secret whenever the need arises, for example the spread of infectious diseases (such as the Corona virus) or crimes, as working to conceal them leads to Its spread and harm to the public interest, but this does not mean absolute disclosure of the secret through this, it can be said that the professional secret is no longer an obstacle to protecting the public interest. With regard to professional confidentiality, the professional may disclose the secret whenever necessary, with the duty to respect the restrictions established by the law. If the professional violates or exceeds them, he or she is considered
Keywords: الموظف العمومي -السر المهني -